The unified theory – Neurology of emotions and how to control them - Cherian, Iype; Burhan, Hira; Kaur, Harshpreet; Shreewastav, Rupesh Kumar (Journal of Nobel Medical College, 2018)
Introduction: The major emotions such as fear, anger, joy and sadness are created through a complex mechanism in the temporal lobe combining data from all the sensory inputs to the brain. However, these emotions may turn into extreme manifestations when the hypothalamus and the autonomic nervous system transform these emotions to panic, rage, orgasm/laughter and grief. The Papez circuit which is at play for this “different turn” may be inactivated or could be over ridden by forebrain activity, that is, sequencing. This probably was the reason to the old adage of counting to ten when one is emotional. In this article, we hope to look at the basis and the neurology behind this and formulate a method to overcome panic.Materials & Methods:A pilot study of 10 children aged 10 -16 was done on 16th October 2017. These children were shown pictures inducing fear and anger. A Visual Analogue Score (VAS) was used to determine the induced emotion. Next, the children were made to do sequencing tasks like mathematical calculations while viewing the similar graphics again. The new score was recorded and the data analyzed.Results: The most frequently recorded VAS (n=4) before sequencing was around 6.0, and between 3.0-3.5 post sequencing. The mean VAS without sequencing was 6.19 ± 0.91, which reduced to 3.65 ± 0.665. On comparing the individual VAS scores before and after sequencing, there was a general trend of a decreased VAS post-sequencing. The results were statistically significant with a p-value